Positive and Negative Family Relationships Correlate With Mental Health Conditions -a Systematic Review and Meta-Analysis - Jutta Lindert; Jutta Lindert; Sarah Arndt; Natalie Cook; Paul A. Bain; Ichiro Kawachi (Public Health Reviews)
ObjectivesWe aim to investigate the association between family relationships and mental health conditions in adults aged 18+.MethodsWe conducted a systematic review on associations of family relationships and mental health conditions by searching in databases MEDLINE, Embase, Web of Science Core Collection, PsycINFO, Sociological Abstracts (ProQuest), and PTSDPubs. We calculated the Pearson correlation coefficients and I2 statistics using a random-effects model. Additionally, we investigated publication bias using funnel plots.ResultsOf the 3,707 records screened, 40 with n = 35,634 participants met the inclusion criteria (38.5% male, 59.5% female, mean age 39.57), were conducted mostly in North America (n = 27). Positive family relationships were investigated in 33 studies, negative relationships in 12 studies. Positive family relationships were not statistically significantly associated with depression [r = −0.071 (−0.256, 0.119), p = 0.463, anxiety r = 0.026 (−0.032, 0.084), p = 0.375] or alcohol abuse [r = 0.035 (−0.103, 0.0034), p=0.326]. Positive family relationships were statistically significantly associated with illicit drug use [r = 0.061 (0.025, 0.096), p = 0.001]. Negative family relationships were statistically significantly associated with anxiety [r = 0.075 (0.019, 0.130), p = 0.009], and with depression [r = 0.111 (0.033, 0.188), p = 0.005].ConclusionInterventions reducing negative family relationships can potentially strengthen positive mental health.